Characterization of a HKT-type transporter in rice as a general alkali cation transporter - Golldack, Dortje; Su, Hua; Quigley, Francoise; Kamasani, Uma R.; Muñoz-Garay, Carlos; Balderas, Enrique; Popova, Olga V.; Bennett, John; Bohnert, Hans J.; Pantoja, Omar (Wiley, 2002)
We report the characterization of rice OsHKT1 (Oryza sativa ssp. indica) homologous to the wheat K+/Na+‐symporter HKT1. Expression of OsHKT1 in the yeast strain CY162 defective in K+‐uptake restored growth at mM and µM concentrations of K+ and mediated hypersensitivity to Na+. When expressed in Xenopus oocytes, rice OsHKT1 showed uptake characteristics of a Na+‐transporter but mediated transport of other alkali cations as well. OsHKT1 expression was analysed in salt‐tolerant rice Pokkali and salt‐sensitive IR29 in response to external cation concentrations. OsHKT1 is expressed in roots and leaves. Exposure to Na+, Rb+, Li+, and Cs+ reduced OsHKT1 transcript amounts in both varieties and, in some cases, incompletely spliced transcripts were observed. By in situ hybridizations the expression of OsHKT1 was localized to the root epidermis and the vascular tissue inside the endodermis. In leaves, OsHKT1 showed strongest signals in cells surrounding the vasculature. The repression of OsHKT1 in the two rice varieties during salt stress was different in various cell types with main differences in the root vascular tissue. The data suggest control over HKT expression as a factor that may distinguish salt stress‐sensitive and stress‐tolerant lines. Differences in transcript expression in space and time in different lines of the same species appear to be a component of ion homeostasis correlated with salt sensitivity and tolerance.